Hospital dietary planning system using constraint programming - Noppon Choosri (2018)
© 2015 IEEE. Due to the fact that proper dietary planning will maintain the healthiness of patients, plus a food consumption control is an important clinical treatment of certain diseases of medical healthcare. This paper is aimed at proposing a practical solution to generate an automated schedule for both the In- Patient Department (IPD) and Out-Patient department (OPD) for a hospital. The challenges of this problem is that food to be served is required to have the right amount of nutrients for patients, also some food should not be consumed by patients who have certain diseases. Manual dietary planning is tedious, time- consuming, and requiring experience and knowledge of dietitians. This paper tackles the problem by proposing an information system implemented by an application of database and Constraint Programming. The study has shown that the proposed solution has a potential to improve operations of the case study in Thailand. The developed prototype system can generate a monthly menu for several clinical treatment (i.e. diabetes, kidney diseases, and gout diseases) in a substantially quicker and sophisticate manner than human operated. An evaluation of user satisfaction suggest that the system is relatively satisfactory.